(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chaim Potok’s My Name is Asher Lev focuses on a clash between the secular and the Orthodox Jewish culture. The structural framework of core clash now is extended to a bitter clash between Hasidic Jewish culture and Western art and a clash between father and son. Asher Lev introduces himself to the reader as a painter mired in controversy as an observant Jew and an artist. Asher experiences the existential depression all through his life. Because of his passion in art the people around him feels that he had brought disgrace to their Jewish identity. This research paper attempts to trace the conflict between the secular and orthodox Jewish community through psychoanalytical perspective.